2020
DOI: 10.48550/arxiv.2011.09851
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Digital trace data collection through data donation

Laura Boeschoten,
Jef Ausloos,
Judith Moeller
et al.

Abstract: A potentially powerful method of social-scientific data collection and investigation has been created by an unexpected institution: the law. Article 15 of the EU's 2018 General Data Protection Regulation (GDPR) mandates that individuals have electronic access to a copy of their personal data, and all major digital platforms now comply with this law by providing users with "data download packages" (DDPs). Through voluntary donation of DDPs, all data collected by public and private entities during the course of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…When using the workflow as proposed by Boeschoten et al (2020) and the software as presented in this paper for a research project, the only task that remains is that data scientists and applied researchers collaborate to develop a high-quality extraction script in Python that is flexible in terms of handling a variety of data structures. See Boeschoten et al (2021) for an overview of the data types and structures that are typically found in DDPs from major data controllers.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When using the workflow as proposed by Boeschoten et al (2020) and the software as presented in this paper for a research project, the only task that remains is that data scientists and applied researchers collaborate to develop a high-quality extraction script in Python that is flexible in terms of handling a variety of data structures. See Boeschoten et al (2021) for an overview of the data types and structures that are typically found in DDPs from major data controllers.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Recently, a workflow was introduced that allows researchers to analyse the digital traces found in these DDPs while preserving the privacy of the research participant Boeschoten et al (2020). In this workflow, a research participant downloads the DDP of interest onto their personal device.…”
Section: Introductionmentioning
confidence: 99%
“…Per the EU's GDPR [11], most major digital platforms now provide their users with electronic access to the personal data they have on each user, via downloadable data packages [7]. A prominent movement in the medical field [5,36], researchers studying digital platforms are beginning to leverage the rich information in these packages by requesting that users donate them for study.…”
Section: Data Donationmentioning
confidence: 99%
“…Data controllers are obliged to provide a copy of this personal data in a machine readable format and most large data controllers currently comply with this by providing users with the option to retrieve an electronic "Data Download Package" (DDP). These DDPs contain all data collected by public and private entities during the course of citizens' digital life and form a new treasure trove for social scientists (Boeschoten, Ausloos, Moeller, Araujo, & Oberski, 2020;King, 2011). However, depending on which data controller is used, the data collected through DDPs can be deeply private and potentially sensitive.…”
Section: Introductionmentioning
confidence: 99%